ショウワキチ ニ オケル セイソウケン デンバ デンリュウ ノ カンソク - 田中, 良和; タナカ, ヨシカズ; 小川, 俊雄; オガワ, トシオ; 小玉, 正弘; コダマ, マサヒロ; TANAKA, Yoshikazu; OGAWA, Toshio; KODAMA, Masahiro (国立極地研究所, 1975)
P(論文) The measurements of vector electric fields and currents were made with two plastic balloons of 5,000 m^3 launched from Syowa Station (L=8.4), Antarctica, on 28 November and 29 December, 1972. The results give the following. (1) The vertical electric field and current at the altitude of 30km are 0.12-0.21 V/m and 1.3-2.2 x10^<-12> A/m^2 respectively, and their diurnal variations are roughly consistent with the expected variation from the average world-wide thunderstorm activity. (2) The electrical conductivities were estimated from the ratio of the electric current to the electric field giving the average value of 1 x 10^<-11> mho/m at the altitude of 30 km. This value is about twice as large as that in Japan. This can be explained by the latitudinal effect of the cosmic ray ionization in the atmosphere. (3) Enhancements of the electric field and current were observed in both vertical and horizontal components of the magnitude of about 80 mV/m and 0.8 x 10^<-12> A/m^2 respectively at an initial stage of a magnetic substorm. The vertical electric field on the ground was also correspondingly enhanced by about 80 V/m at the same time. (4) Comparisons of observed horizontal electric field vectors with the magnetic fields observed at Syowa Station show that the magnetic field variations are caused by the ionospheric Hall current. (5) One hour averages of the horizontal electric field show large scale convection fields consistent with S^p_q in the polar ionosphere and with DP-2 in the equatorial magnetosphere. The average ionospheric and magnetospheric equatorial electric fields were 40 mV/m and 0.98 mV/m respectively, and corresponding plasma convection velocities were estimated to be 700 m/s and 22 km/s respectively. departmental bulletin paper